Self-Efficacy as A Factor of Entrepreneurial Intention - Marlina Deliana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze entrepreneurial intention that is influenced by self-efficacy owned by a person based on the theory proposed by Bandura.  Self-efficacy beliefs determine how people feel, think, motivate themselves and behave. Such beliefs produce diverse effects through four main processes namely cognitive, motivational, affective, and selection processes.  Self-efficacy can be developed by four main sources; Personal Experience, Role Model, Social Persuasion, and Psychological and Emotional Conditions Entrepreneurial intention has a relationship to a person's behavior.  Self-Efficacy is closely related to actions that are influenced by one's feelings, way of thinking, and motivation. Self-efficacy possessed by a person can determine how a person can take opportunities with the abilities possessed. The determining factors of success and failure and how a person can immediately rise from failure are also greatly influenced by the self-efficacy possessed. The determination of one's career and desire to succeed and succeed depends on the self-efficacy a person has, including the desire to start a business. The higher a person's self-efficacy, the higher the chance of the person being able to decide whether his desire will be successfully achieved or not based on the abilities possessed.